Skin-to-skin contact and delivery room practices: a longitudinal survey conducted in Piedmont and the Aosta Valley - Michelangelo Barbaglia; Enrico Finale; Silvia Noce; Alessandro Vigo; Cesare Arioni; Raffaella Visentin; Elisabetta Scurati-Manzoni; Andrea Guala; SUPC Piedmont and Aosta Valley study group (BMC, 2019)
Abstract Background Sudden unexpected postnatal collapse of presumably healthy neonates during early skin-to-skin contact is a rare, yet recognized occurrence, associated with a high risk of mortality and morbidity. A survey was conducted in 2012 in 30 delivery wards throughout Piedmont and the Aosta Valley to evaluate the environmental and logistical aspects that could be linked to SUPC. The survey was again conducted in 2016 in 28 delivery wards in Piedmont and the Aosta Valley in order to evaluate organizational improvements introduced after ministerial indications and recommendations by the Italian Society of Neonatology were published in 2014, in light of new findings regarding the phenomenon. Methods A questionnaire specifically asking about the organization of delivery wards, and surveillance or supervision during early skin-to-skin contact, was sent to all of the hospitals taking part in the survey in both 2012 and 2016. The collected data were elaborated anonymously and the statistical analysis was performed by using the two by two table. Results In 2012, 28 out of 30 delivery wards in Piedmont and Aosta, with a total of 31,074 newborns out of 35,435, were evaluated in all of the environmental and logistical aspects that might be cause for SUPC to occur. An identical survey was taken again in 2016; 26 out of 28 wards participated with a total of 27,484 newborns out of 30,339. In 2012, early skin-to-skin contact took place immediately in all the delivery rooms in 27 wards, and soon after in the post-partum room in one; in 11 out of 28 wards there was early skin-to-skin contact in the operating theater itself, following caesarean sections (11/26 in 2016). Routine newborn care was given after 3 h in 8 delivery wards (7/26 in 2016); after 2 h in 12 (7/26 in 2016); after 1 h in 2 (4/26 in 2016); after 30 min in 3 (2/26 in 2016); after 10 min in 1 (0/26 in 2016); after 1 or 2 min in 1 (0/26 in 2016) and at any time in one ward (6/26 in 2016). Conclusion Periodic surveys of delivery wards are useful for the assessment of all the aspects and risk factors that need to be changed in order to implement safe early skin-to-skin contact.